Evaluasi Program Double Track dalam Meningkatkan Kemampuan Berwirausaha Siswa di SMA Negeri se-Kabupaten Trenggalek - Restu Nur Cholidah; Bambang Budi Wiyono; Ahmad Yusuf Sobri (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The Double Track Program has become an innovative strategy in improving student competency at State Senior High Schools (SMA) in Trenggalek Regency. This article presents the results of an evaluation of the implementation of the program at SMA Negeri 1 Panggul and SMA Negeri 1 Tugu. It was found that this program had a positive impact in developing students' practical and academic skills, as well as strengthening the school's educational image. Despite facing obstacles such as limited funding and lack of equipment, efforts continue to be made to increase its effectiveness. The role of school principals, trainers, facilitators and administrative officers is very important in implementing this program. Program evaluation is carried out by paying attention to alumni achievements, the number of new registrants, and the growth of students' entrepreneurial spirit. Suggestions are provided to improve program performance through evaluation of planning documents, marketing strategies, and organizing lessons on marketing to students. Despite facing funding constraints, student and teacher enthusiasm is high, and the results achieved are satisfactory, showing that the double track program has succeeded in empowering students with relevant skills for their future and improving the reputation of education in the school environment.